2012
DOI: 10.1111/ocr.12003
|View full text |Cite
|
Sign up to set email alerts
|

Orthodontic miniscrew failure rate and root proximity, insertion angle, bone contact length, and bone density

Abstract: While bone contact length, miniscrew angle, and bone density did not exert major effects on miniscrew failure, root proximity was the factor that most affected miniscrew failure, especially for miniscrews placed in the mandible. CBCT was superior to periapical dental X-rays for evaluating the proximity of miniscrews to the root. Correction of the X-ray attenuation coefficient value was necessary for measuring bone density using CBCT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
1
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(81 citation statements)
references
References 20 publications
(27 reference statements)
3
74
1
3
Order By: Relevance
“…This suggests that screws have greater mobility in the mandible than in the maxilla regardless of root proximity. Higher failure rate in the mandible in previous reports (18,22), and higher risk for failure of the mandibular screws in this study might be related to the higher mobility (PTV: approximately 3 in category A) in the mandible. In the mandible, a PTV of approximately 3 may be acceptable mobility to withstand orthodontic force, because there was no significant difference between the success rates for the maxilla and mandible in this study.…”
Section: Discussioncontrasting
confidence: 38%
See 1 more Smart Citation
“…This suggests that screws have greater mobility in the mandible than in the maxilla regardless of root proximity. Higher failure rate in the mandible in previous reports (18,22), and higher risk for failure of the mandibular screws in this study might be related to the higher mobility (PTV: approximately 3 in category A) in the mandible. In the mandible, a PTV of approximately 3 may be acceptable mobility to withstand orthodontic force, because there was no significant difference between the success rates for the maxilla and mandible in this study.…”
Section: Discussioncontrasting
confidence: 38%
“…CBCT gives an undistorted view of the dentition, which can be used to accurately visualize erupted and non-erupted teeth, orientation of the tooth root, and anomalous structures that cannot be satisfactorily visualized with conventional two-dimensional radiography (17). Recently, Watanabe et al (18) used CBCT to evaluate the relationship between root-screw distance and screw stability and found that CBCT was better than periapical dental radiographs for evaluating the proximity of miniscrews to the root.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23] Prevention of miniscrew failure thus requires meeting 2 crucial conditions: increased mechanical stability, achieved by increasing the contact area between the miniscrew and the cortical bone, 18 and prevention of root proximity by shortening the miniscrew. 23 However, increasing the miniscrew diameter to enhance the mechanical stability also increases the risk of root proximity, whereas decreasing the miniscrew diameter decreases the risk of root proximity. As a result, no currently available miniscrews or skeletal anchorage devices meet these conditions while remaining minimally invasive.…”
mentioning
confidence: 99%
“…Alguns trabalhos relataram que a espessura da cortical e densidade óssea, a qualidade e inflamação do tecido mole peri-implantar, o design do mini-implante, técnica cirúrgica e a carga excessiva aplicada são alguns dos fatores que podem influenciar na perda desta estabilidade (CHENG et al, 2004;KRAVITZ;KUSNOTO, 2007;MIYAWAKI et al, 2003;KWON, 2006). A partir de estudo em humanos com radiografias periapicais e tomografia computadorizada, Kuroda et al (2007) afirmaram que a proximidade dos mini-implantes com as raízes dos dentes adjacentes constitui o principal fator de falha destes dispositivos, principalmente na mandíbula, resultado semelhante encontrado por Watanabe et al (2013) Ressaltaram ainda que mini-implantes inseridos manualmente podem penetrar na dentina radicular.…”
Section: Lesões Radiculares Provocadas Por Mini-implantesunclassified
“…A avaliação do contato/perfuração radicular por mini-implantes geralmente tem sido feita através de análise histológica (AHMED et al, 2012;ASSCHERICKX et al, 2005;BRISCENO et al, 2009;SHIN;KYUNG, 2008;DAO et al, 2009;KIM, 2011;LEE et al, 2010;MAINO et al, 2007;RENJEN et al, 2009) TASDEMIR, 2011;HWANG, 2011;KURODA et al, 2007;MCCABE;KAVANAGH, 2012), muitas vezes limitadas por ser tratar de imagens bidimensionais (ASSCHERICKX et al, 2008), e por tomografia computadorizada de feixe cônico (KURODA et al, 2007;SHIGEEDA, 2014;SHINOHARA et al, 2013;SON et al, 2014;WATANABE et al, 2013) (BARROS et al, 2011;FLORVAAG et al, 2010;HWANG, 2008;WILMES et al, 2008a;DRESCHER, 2008). Quando a colocação dos mini-implantes é realizada sem perfuração prévia, exige-se mais força de torção para inserção SHIN;KYUNG, 2008;MASSIF;FRAPIER;MICALLEF, 2007;MISCHKOWSKI et al, 2008 Ainda na tabela 4, observa-se que não houve uma relação direta entre o aumento do diâmetro dos mini-implantes com o aumento do torque de inserção, relação esta tão frequente na literatura (BARROS et al, 2011;FLORVAAG et al, 2010;HWANG, 2008;WILMES et al, 2008a;…”
Section: Microtomografia Computadorizadaunclassified